2014
DOI: 10.1016/j.jpha.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of gouty arthritis' biomarkers in human urine using reversed-phase high-performance liquid chromatography

Abstract: Creatinine, uric acid, hypoxanthine and xanthine are important diagnostic biomarkers in human urine for gouty arthritis or renal disease diacrisis. A simple method for simultaneous determination of these biomarkers in urine based on reversed-phase high-performance liquid chromatography (RP-HPLC) with ultraviolet (UV) detector was proposed. After pretreatment by dilution, centrifugation and filtration, the biomarkers in urine samples were separated by ODS-BP column by elution with methanol/50 mM NaH2PO4 buffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
(29 reference statements)
0
25
0
Order By: Relevance
“…Thus, the detection of UA has the vital significance in the field of clinical diagnosis. Several methods, such as enzymatic [12], voltammetric [13], high performance liquid chromatographic [14], and phospho-tungstic acid deoxidizing methods, have been utilized for the detection of UA. Because DA and UA always coexist in human biological fluids, it is highly desirable to propose a selective, sensitive and simultaneous detection technique for analytical research and diagnostic applications Electrochemical methods with advantage of sensitivity, rapidity and low cost have been widely adopted for the simultaneous detection of UA and DA [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the detection of UA has the vital significance in the field of clinical diagnosis. Several methods, such as enzymatic [12], voltammetric [13], high performance liquid chromatographic [14], and phospho-tungstic acid deoxidizing methods, have been utilized for the detection of UA. Because DA and UA always coexist in human biological fluids, it is highly desirable to propose a selective, sensitive and simultaneous detection technique for analytical research and diagnostic applications Electrochemical methods with advantage of sensitivity, rapidity and low cost have been widely adopted for the simultaneous detection of UA and DA [15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In this test, alkaline picrate reacts with creatinine to form an orange-red product that is measured spectrophotometrically. Other current methods include HPLC-MS/MS [2], HPLC-DAD [3,4], spectrophotometry [5], spectrophotometry using a portable microfluidic system [6], and electrophoresis with electrochemical [7], UV [8], and colorimetric detection [9].…”
Section: Introductionmentioning
confidence: 99%
“…Analytical procedures for the measurement of uric acid include HPLC-DAD [3,4], electrophoresis with UV detection [8], spectrophotometry with chemometric tools [12], electrochemical methods [13], colorimetric detection with multiple indicators [14], enzymatic reaction [15], and gold nanoparticles [16]. Only methods that involve separation techniques, such as chromatography [3,4] and electrophoresis [8], are able to determine both analytes simultaneously. However, these techniques involve the use of large volumes of toxic organic solvents, produce substantial amounts of waste that may be dangerous to the operator and the environment [17], and require laborious clean-up steps.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly excreted in the urine (Huda et al, 2014;Ferin et al, 2013). Urine, serum and saliva samples have been extensively investigated for the UA assay in biological specimens (Shibasaki et al, 2012;Punzi and So, 2013;Xiang et al, 2014). In recent years, several methods have been presented by different researchers for the determination of UA in biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well known that UA is present in saliva (Stibůrková et al, 2014;Chauhan et al, 2014). Urine, serum and saliva samples have been extensively investigated for the UA assay in biological specimens (Shibasaki et al, 2012;Punzi and So, 2013;Xiang et al, 2014). However, to the best of our knowledge, the study of gout based on the determination of UA in human fingernails has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%